Effect of Calcination Temperature of SiO2-TiO2 Composite XRD Characterization of Crystal Size Structure and Phase - Putri, Sri Fany Mulya; Ratnawulan, Ratnawulan; Gusnedi, Gusnedi; Jonuarti, Riri (Department of Physics, Universitas Negeri Padang, 2024)
Calcination is often used to activate beneficial metal oxidation in catalysts and improve material stability. In the metal oxidation research used is SiO2-TiO2 nanocomposite because it has advantages over photocatalysts and thermal stability. One important factor that affects is the particle size and crystal phase formed during the calcination process at various temperatures. The purpose of the study was to determine the effect of calcination on changes in phase and crystal structure in SiO2-TiO2 nanocomposites. The material used for the manufacture of nanocomposites is natural silica source from coconut fiber which is burned into white ash. The ash was extracted for the preparation of silica sol by adding Tetraethyl Orthosilicate (TEOS) as a precursor synthesized by the sol gel method then, calcination was carried out with temperature variations of 700 , 800 , and 900 . After calcination, XRD characterization was carried out to obtain crystal sizes of 63.48 nm, 66.87 nm, and 73.83 nm. The phase formed is dominant in TiO2 is rutile and SiO2 is quartz and cristobalite.